2003
DOI: 10.1186/1471-2156-4-s1-s34
|View full text |Cite
|
Sign up to set email alerts
|

Strategy and model building in the fourth dimension: a null model for genotype × age interaction as a Gaussian stationary stochastic process

Abstract: Background: Using univariate and multivariate variance components linkage analysis methods, we studied possible genotype × age interaction in cardiovascular phenotypes related to the aging process from the Framingham Heart Study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 16 publications
1
43
0
Order By: Relevance
“…It can be shown that in the absence of a genotype-environment interaction (null hypothesis): (1) the genetic variance (σ G 2 ) will be homogenous across the levels of environmental exposure; and (2) the same quantitative trait measured in participants living in different levels of environmental exposure (e.g. active vs inactive or different ages) will have a genetic correlation (ρ G ) of 1.0 [5,25,27]. Hence, the presence of genotype-environment interactions is determined by testing two null hypotheses, which for the sake of simplicity will be referred to as class 1 and class 2 interactions from here on.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…It can be shown that in the absence of a genotype-environment interaction (null hypothesis): (1) the genetic variance (σ G 2 ) will be homogenous across the levels of environmental exposure; and (2) the same quantitative trait measured in participants living in different levels of environmental exposure (e.g. active vs inactive or different ages) will have a genetic correlation (ρ G ) of 1.0 [5,25,27]. Hence, the presence of genotype-environment interactions is determined by testing two null hypotheses, which for the sake of simplicity will be referred to as class 1 and class 2 interactions from here on.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…A low-degree polynomial may be adequate to model the change in variance over time but inadequate for approximating the covariance structure or vice versa. Alternative models that fit separate functions for the change in variance and the change in correlation or covariance have been proposed for polygenic effects (character process models, e.g., Pletcher and Geyer 1999;Diego et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals in this cohort were randomly selected from the community, with the constraints that they are of MexicanAmerican ancestry, are part of a large family, and live within the San Antonio region (see ref. 50 for recruitment details). No other inclusion or exclusion criteria were imposed.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the discrete two-environment model is extended to reflect pairwise differences in environment between subjects, thereby sampling the full range of subject ages in the cross-sectional sample (21,50,51). The hypothesis in the extended model is that the phenotypic covariance between individuals is a function of interaction between their similarity in age and their genetic similarity.…”
Section: Methodsmentioning
confidence: 99%